Edukasi dan Peningkatan Kesadaran dari Segi Kesehatan dalam Rangka Percepatan Pencegahan Penanganan Covid-19 pada Pedagang Pasar Kota Palangka Raya - Fera Sartika; Risqika Yuliatantri Paramawidhita; Suratno Suratno (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2021)
Market traders are the people most at risk of being infected with Coronavirus Disease (COVID-19). Transaction activities in the market between sellers and buyers are high, so awareness is very important to implement the COVID-19 preventive health protocol recommended by the government. The target of this activity is traders in the Pasar Besar City of Palangka Raya, Central Kalimantan. The purpose of this activity is to increase knowledge and awareness in implementing health protocols in the market in order to accelerate the prevention of handling COVID-19. The method of this activity is by conducting surveys through questionnaires, providing education and training/demonstrations in implementing health protocols in the market, and distributing leaflets, masks, and hand sanitizers. This community service activity focuses on education, socialization, and training/demonstration of the application of health protocols in the market for 72 traders in the market, which includes: (1) wearing masks; (2) perform hand hygiene; (3) avoiding touching the face area, (4) applying proper etiquette coughing or sneezing; and (5) maintaining a distance (at least 1 meter) from other buyers/traders.